A CLOSE ENCOUNTER OF THE LITERARY KIND: AN EXAMPLE OF THE LITERARY ANALYSIS AT A SEMINAR FOR PRIMARY AND SECONDARY SCHOOL TEACHERS - Наташа В. Кампмарк (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2012)
The paper gives an example of a literary analysis of a prose extract conducted at a teacher education seminar attended by primary and secondary school English teachers. Multiple aims of the analysis have been presented in relation to the function of the literary text in language teaching. The literary text is approached as a cultural artefact, as an instrument of language teaching, and as a stimulus for personal growth. As a result, the process of text analysis had a threefold aim: (1) to introduce the candidates to authors and their works, and cultural elements; (2) to practise strategies of using a literary text as a vehicle for development of linguistic skills; and (3) to practise methods and strategies of literary analysis and independent critical thinking.